SOFTWARE MODELING OF FRICTION PENDULUM WITH UPLIFT RESTRAINERS (Revista Internacional de Ingeniería de Estructuras, 2023)
The rational application of seismic isolation can reduce substantially of the inertial forces developed in the superstructure during a strong earthquake. These lateral forces reduction is also associated to important reductions in overturning moments. However, tensile forces and uplift demands still can be very large for tall and slender buildings. This could be a design issue worth caring about, as conventional sliding isolators and friction pendula are uncapable of resisting gracefully significant tensile forces and uplift demands. However, there have already been proposed friction pendulum capable of taking tensile forces and restrain uplifts. In this paper, the authors summarize how this friction pendulum work and show can they be modeled in a practical way combining several elements available in ETABS. The proposed ETABS modeling is calibrated and compared with experimental results reported in the literature, obtaining good approximations.